2015
DOI: 10.1016/j.ddmod.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Computational models of ventilator induced lung injury and surfactant dysfunction

Abstract: Managing acute respiratory distress syndrome (ARDS) invariably involves the administration of mechanical ventilation, the challenge being to avoid the iatrogenic sequellum known as ventilator-induced lung injury (VILI). Devising individualized ventilation strategies in ARDS requires that patient-specific lung physiology be taken into account, and this is greatly aided by the use of computational models of lung mechanical function that can be matched to physiological measurements made in a given patient. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…A number of theoretical and experimental studies have demonstrated that the increase in viscosity and surface tension of airway surface liquid likely results in VILI. Two main physical mechanisms for VILI are lung tissue overdistention caused by surface tension-induced alterations in interalveolar micromechanics and atelectrauma to the epithelial cells during repetitive airway reopening and closure [3941]. The prediction from an adjoining two-alveoli model by Chen et al [42] shows that the pattern of alveolar expansion can appear heterogeneous or homogeneous, strongly depending on differences in air-liquid interface tension on alveolar segments.…”
Section: Importance Of Rheological Measurements Of Airway Surface Liquidmentioning
confidence: 99%
“…A number of theoretical and experimental studies have demonstrated that the increase in viscosity and surface tension of airway surface liquid likely results in VILI. Two main physical mechanisms for VILI are lung tissue overdistention caused by surface tension-induced alterations in interalveolar micromechanics and atelectrauma to the epithelial cells during repetitive airway reopening and closure [3941]. The prediction from an adjoining two-alveoli model by Chen et al [42] shows that the pattern of alveolar expansion can appear heterogeneous or homogeneous, strongly depending on differences in air-liquid interface tension on alveolar segments.…”
Section: Importance Of Rheological Measurements Of Airway Surface Liquidmentioning
confidence: 99%
“…The greatest progress in the treatment of acute respiratory diseases has been mechanical ventilation. While use of mechanical ventilation has significant therapeutic benefits, improper use of this treatment (such as excessive usage time or incorrect parameter settings), may lead to or aggravate damage to the patient's lung tissue through various mechanisms, which is called ventilator-induced lung injury (VILI)1. To improve the therapeutic outcomes of patients who require mechanical ventilation, clarification of the mechanism of VILI and the development of new approaches for its prevention warrant further study.…”
Section: Introductionmentioning
confidence: 99%
“…It also includes increased vascular permeability, heterogeneous alveolar atelectasis and consolidated lung regions resulting in low ventilation to perfusion lung units, lung oedema, and progressive deterioration in FRC. Finally, the neonates and adults share a reduction in lung compliance and pulmonary artery hypertension when they develop acute respiratory distress [85,100,101].…”
Section: Surfactant and The Adult Population With And Without Ali/ardsmentioning
confidence: 99%